A magnetically driven Janus nanomotor with mucus inertness and its preparation method and application
By grafting pCB on the surface of the Janus magnetically driven nanomotor composed of Fe3O4 nanoparticles and mesoporous silica nanorods, Janus-MMSN-pCB is solved, and an efficient mucosal drug delivery carrier is achieved .
Patent Information
- Application Number
- CN202211264863.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-17
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-10-17
AI Technical Summary
The prior art is difficult to penetrate the mucus layer efficiently, limiting the effectiveness of mucosal administration, especially in areas where mucus is rapidly renewed, such as the eyes and respiratory tract.
Janus magnetically driven nanomotor consisting of Fe3O4 nanoparticles and mesoporous silica nanorods were used, and the zwitterionic polymer pCB was grafted on its surface to form Janus-MMSN-pCB. The nanomotor can move autonomously in an external magnetic field and quickly penetrate the mucus layer through the superhydrophilic and electrical neutrality of the pCB.
Janus-MMSN-pCB can efficiently penetrate the mucus layer under a magnetic field, with mucus permeability reaching 42.59±4.17%, and a movement speed of 5.42±0.53μm/s. It is low toxicity to mucus-producing cells and has a good biological phase. Capacity.
Smart Images

Figure CN115624629B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of biomedicine technology and relates to a magnetically driven Janus nanomotor with mucus inertness, a preparation method and an application thereof. Background Art
[0002] Mucous membranes are widely distributed in the human body as an important immune defense line to prevent pathogenic microorganisms from invading the human body. They can secrete mucus to cover the mucosal epithelial cells to form a mucus layer. The mucus layer is a viscoelastic hydrogel composed of mucin, water, inorganic salts, peptides, bacteria, and epithelial cell fragments (Acta Biomaterialia, 2020, 119: 13-29), which plays an important role in the function of mucosal immunity (Lab on a Chip, 2018, 18 (21)). The mucus layer relies on size exclusion and mucus adhesion to prevent foreign particles from entering mucosal epithelial cells (Advanced Drug Delivery Reviews, 2019, 142: 62-74). Intermolecular interactions such as electrostatic and hydrophobic interactions are the main sources of the adhesion ability of the mucus layer (Asian Journal of Pharmaceutical Sciences, 2015, 10 (4): 275-282). However, while protecting the human body, the mucus layer also acts as a mucus barrier to limit the penetration of micro-nanocarriers used for mucosal delivery.
[0003] The use of micro-nano carriers to penetrate the mucus layer for mucosal drug delivery is a promising drug delivery method. Drugs delivered through the mucosa can produce local therapeutic effects or be absorbed through the mucosa into the systemic circulation to exert systemic therapeutic effects. However, how to efficiently penetrate the mucus layer has become one of the key issues that must be addressed in this drug delivery method. In recent years, mucus penetrating particles (MPPs) that can penetrate the mucus barrier and accumulate on the surface of mucosal epithelial cells have attracted widespread attention. MPPs have hydrophilicity similar to that of viruses, an electrically neutral surface (i.e., a mucus inert surface), and a sufficiently small volume, which can weaken the interaction between particles and mucus and quickly penetrate the mucus layer (Advanced Therapeutics, 2021, 4(2)). The preparation of MPP mainly relies on the modification of hydrophilic and electrically neutral materials on nanocarriers. Mesoporous silica nanorods (MSN) are a common nanocarrier with large surface area, adjustable size, easy modification and good biocompatibility. They are considered to be a good medical nanomaterial (Nano Research, 2015, 8(3): 751-764). Poly(ethylene glycol) (PEG) is a commonly used MPP modification material. At present, a variety of MSN modified with PEG or its copolymers have been developed as drug delivery carriers in the human body. However, studies have found that PEG can inhibit cellular uptake and may also produce adverse reactions such as neutralizing antibodies (YakugakuZasshi, 2020, 140(2): 163-169; Acta Biomaterialia, 2016, (43): 61-70). Finding new sticky and inert modified materials has become a trend. With the in-depth study of zwitterionic polymers with equal amounts of anionic and cationic groups (neutral charge) and superhydrophilicity, polycarboxybetaine methacrylate (pCB) has gradually been developed as a highly hydrophilic anti-protein adsorption material. Studies have shown that pCB is an excellent material with good biocompatibility, strong anti-adsorption ability and easy functionalization (Acta Pharmaceutica Sinica, 2019, 54(3): 547-554; Colloids and Surfaces A Physicochemical and Engineering Aspects, 2021, 617: 126369).
[0004] In addition, the mucus layer is regularly renewed (Molecular Pharmaceutics, 2020, 17(6): 1899-1909). Although MPP can penetrate the mucus layer, the renewal time of some mucus layers in the human body is very short. For example, the renewal cycle of ocular mucus is about 5-8 minutes (Advanced Drug Delivery Reviews, 1993, 11(3): 349-383), and the respiratory mucus is renewed every 10-30 minutes (Current Drug Delivery, 2006, 3(3): 275-285; Laryngoscope, 2010, 117(5): 932-938). The renewal of the mucus layer will remove the MPP trapped in it from the body. Although many MPPs have been synthesized, they cannot fully meet the needs of practical applications. Further accelerating the penetration rate of MPP into the mucus layer is of great significance for the completion of the delivery process. Preparing nanocarriers into nanomotors with mobility is a feasible way to increase the delivery speed (Therapeutic Delivery, 2018, 9(4): 303-316). Nanomotors are nanoscale devices that can convert different forms of energy into their own driving force. They have been widely studied for drug delivery in the human body, but there are no reports on the application of nanomotors in mucosal drug delivery. Combining nanomotor preparation technology with MPP to obtain nanocarriers with mobility and then quickly penetrate the mucus layer is a highly promising mucosal drug delivery strategy. Nanomotors were originally driven by chemical fuels, but the toxicity of fuels such as hydrogen peroxide and hydrazine to human tissues has limited their application in medicine (Materials Review, 2017, 31(S2): 189-193). In order to overcome the defects of chemical fuels, nanomotors driven by external stimuli such as light, electricity, sound and magnetism have been constructed. Among them, nanomotors driven by magnetic fields (MF) can not only use low-intensity magnetic fields to achieve non-destructive remote precision motion control in vivo, but are also suitable for a variety of liquid environments (Science & Technology Review, 2017, 35(18): 39-43; Science & Technology Review, 2017, 35(18): 39-43). 3 O 4 The surface of nanoparticles is easy to functionalize and can move under the guidance of an external magnetic field, making it an ideal magnetically driven nanomotor material (Applied Sciences, 2021, 11(23): 11301).
[0005] Previously, Zhang et al. successfully3 O 4 Nanoparticles and mesoporous silica nanorods were combined to prepare Janus nanoparticles with asymmetric structure (Chemical Communications, 2011, 47, 1225-1227), which is based on Fe 3 O 4 Nanoparticles and mesoporous silica nanomaterials provide the possibility to construct mucus layer penetrating micro-nanoparticles with autonomous movement capabilities. Summary of the invention
[0006] In order to solve the problem of mucus barrier penetration in micro-nanoparticle-mediated mucosal delivery, the present invention adopts the method of Liu et al. (Angewandte Chemie International Edition, 48: 5875-5879) to synthesize Fe 3 O 4 Nanoparticles, and the mesoporous silica nanorods were placed on Fe using the method of Zhang et al. (Chemical Communications, 2011, 47: 1225-1227). 3 O 4 The nanoparticles were grown to prepare magnetically driven Janus nanomotors, which were denoted as Janus-MMSN. Meanwhile, the present invention prepared carboxybetaine methacrylate using the method of Zhang et al. (Langmuir, 2006, 22(24): 10072-10077), and its nuclear magnetic resonance hydrogen spectrum was shown in Figure 2 . Based on the super hydrophilicity and electrical neutrality of pCB, the present invention grafts pCB onto the mesoporous silica surface of Janus-MMSN through atom transfer radical polymerization to prepare a nanomotor that can be driven by a magnetic field (MF), named Janus-MMSN-pCB. Janus-MMSN-pCB can move in a directed manner in an external magnetic field. At the same time, the large amount of pCB contained on its surface makes it highly hydrophilic and can quickly penetrate the mucus layer and enter the mucosal epithelial cells. The purpose of the present invention is to prepare an MPP that can move autonomously and can quickly penetrate the mucus layer to achieve efficient mucosal drug delivery.
[0007] The Janus-MMSN-pCB synthesized by the present invention has good anti-mucus adhesion performance and movement ability in a magnetic field environment. In vitro experiments show that the mucus permeability of Janus-MMSN-pCB in a magnetic field is as high as 42.59±4.17% in 4 hours and the movement speed in mucus reaches 5.42±0.53μm / s, which is 14.11±1.38 body lengths / s. In addition, Janus-MMSN-pCB has low toxicity to mucus-producing Calu-3 cells and has good biocompatibility. In vitro experimental results show that Janus-MMSN-pCB can be taken up by Calu-3 cells within 4 hours. In addition, the Janus-MMSN-pCB synthesized by the present invention has a large mesoporous space and a large number of easily modified surface amino groups, which can be used as a nanocarrier and can be used as a nanocarrier that quickly penetrates the mucus layer.
[0008] The technical solution of the present invention is as follows:
[0009] A method for preparing a magnetically driven Janus nanomotor with mucus inertness; the method is characterized in that a zwitterionic polymer polycarboxybetaine methacrylate pCB is grafted onto a Fe 3 O 4 Nanoparticles and mesoporous silica nanorods MSN on the mesoporous silica surface of the Janus nanomotor driven by a magnetic field MF; the mucus-inert magnetically driven Janus nanomotor is denoted as Janus-MMSN-pCB.
[0010] A method for preparing a magnetically driven Janus nanomotor with mucus inertness comprises the following steps:
[0011] 1) Amino modification of Janus-MMSN surface: A 4-5 mg / mL Janus-MMSN suspension was prepared in anhydrous toluene and placed in a flask, which was placed in an oil bath at 80-85°C. 3-Aminopropyltriethoxysilane was added thereto at a mass ratio of Janus-MMSN to 3-aminopropyltriethoxysilane of 1:18-19, and the aminated product was obtained by reflux for 12-14 h and recorded as Janus-MMSN-NH 2 ;
[0012] 2) Janus-MMSN-NH 2 Surface bromination: Prepare 4-5 mg / mL Janus-MMSN-NH 2 The suspension was placed in an ice bath and the Janus-MMSN-NH 2Triethylamine was added at a mass ratio of 1:8.5-9, and then 0.5-0.55 mg / mL α-bromoisobutyryl bromide solution was prepared with N,N-dimethylformamide and added dropwise to the reaction solution, wherein Janus-MMSN-NH 2 The mass ratio of α-bromoisobutyryl bromide to α-bromoisobutyryl bromide is 1:18-19. After reacting for 2-2.3 hours with magnetic stirring, the mixture is transferred to a 30-35°C water bath for reaction for 17-19 hours. The product is washed to obtain surface brominated nanoparticles, which are denoted as Janus-MMSN-Br.
[0013] 3) Grafting pCB on the surface of Janus-MMSN-Br: N,N-dimethylformamide and water were mixed in a volume ratio of 1:1-1.1 to prepare a solution, Janus-MMSN-Br was dispersed in the above solution at a concentration of 5-6 mg / mL, and pCB monomer was added thereto, the mass ratio of Janus-MMSN-Br to pCB monomer was 1:22-24, and the mass ratio of copper bromide to Janus-MMSN-Br was 1:22- 23 and the mass ratio of 2,2'-bipyridine to Janus-MMSN-Br is 1:3.1-3.3. Copper bromide and 2,2'-bipyridine are added thereto in sequence, and nitrogen is passed through under magnetic stirring. Then, cuprous bromide is added thereto at a mass ratio of cuprous bromide to Janus-MMSN-Br of 1:6.5-7.5. The reaction is terminated after 3-3.5 hours, and the product is washed to obtain a mucus-inert magnetically driven Janus nanomotor, which is recorded as Janus-MMSN-pCB.
[0014] In step 2), Janus-MMSN-NH 2 The mass ratio of α-bromoisobutyryl bromide to α-bromoisobutyryl bromide is 1:18.5-19.
[0015] In the step 3), the mass ratio of Janus-MMSN-Br to pCB monomer is 1:22-23.
[0016] The mucus-inert magnetic field-driven Janus nanomotor (Janus-MMSN-pCB) of the present invention has the ability to resist mucus layer adsorption and can quickly move through the mucus layer in a magnetic field. Its mucus permeability under a magnetic field for 4 hours is as high as 42.59±4.17%, and its movement speed in mucus reaches 5.42±0.53μm / s, which is 14.11±1.38 body lengths / s.
[0017] The mucus-inert magnetically driven Janus nanomotor (Janus-MMSN-pCB) of the present invention has very low toxicity to mucus-producing Calu-3 cells and can be efficiently taken up by Calu-3 cells within 4 hours.
[0018] The specific instructions are as follows:
[0019] The present invention provides a method for preparing a magnetically driven Janus nanomotor with mucus inertia, characterized in that Fe 3 O 4 The magnetically driven Janus nanomotor was prepared by growing mesoporous silica nanorods on nanoparticles, and then the zwitterionic polymer pCB was grafted onto the mesoporous silica surface of the nanomotor. The specific synthesis process is shown in Figure 1 , wherein the structural formula of the pCB monomer is as follows:
[0020]
[0021] The preparation method of a magnetically driven Janus nanomotor with mucus inertness of the present invention comprises the following steps:
[0022] 1) Amino modification of Janus-MMSN surface: 4-5 mg / mL Janus-MMSN suspension was prepared with anhydrous toluene and ultrasonically dispersed in a flask. Then, the suspension was placed in an oil bath at 80-85°C. 3-aminopropyltriethoxysilane was added according to the mass ratio of Janus-MMSN to 3-aminopropyltriethoxysilane of 1:18-19. The suspension was refluxed with a condenser for 12-14 h to obtain an amino product, which was recorded as Janus-MMSN-NH 2 , washed with anhydrous toluene and anhydrous ethanol respectively, and freeze-dried in vacuum for later use;
[0023] 2) Janus-MMSN-NH 2 Surface bromination: Prepare 4-5 mg / mL Janus-MMSN-NH 2 The suspension was added to a three-necked flask and placed in an ice bath. 2 Triethylamine was added in a mass ratio of 1:8.5-9, and after being fully mixed, 0.5-0.55 mg / mL α-bromoisobutyryl bromide solution was prepared with N,N-dimethylformamide and added dropwise to the reaction solution, wherein Janus-MMSN-NH 2 The mass ratio of α-bromoisobutyryl bromide to α-bromoisobutyryl bromide is 1:18-19, and the mixture is stirred under magnetic stirring for 2-2.3 hours in an ice bath, then transferred to a 30-35°C water bath for 17-19 hours, and the product is washed with N,N-dimethylformamide, toluene and deionized water to obtain surface brominated nanoparticles, which are denoted as Janus-MMSN-Br, and then freeze-dried in vacuum for later use;
[0024] 3) Grafting pCB on the surface of Janus-MMSN-Br: N,N-dimethylformamide and water were mixed in a volume ratio of 1:1-1.1 to prepare a solution, and Janus-MMSN-Br was dispersed in a three-necked flask containing the above solution at a concentration of 5-6 mg / mL. Then, pCB monomer was added thereto, and the mass ratio of Janus-MMSN-Br to pCB monomer was 1:22-24, and the mass ratio of copper bromide to Janus-MMSN-Br was 1:22-23 and 2,2' -The mass ratio of bipyridine to Janus-MMSN-Br is 1:3.1-3.3. Copper bromide and 2,2'-bipyridine are added thereto in sequence. Nitrogen is passed through the system under magnetic stirring to remove oxygen. Then, cuprous bromide is quickly added thereto at a mass ratio of cuprous bromide to Janus-MMSN-Br of 1:6.5-7.5. The reaction is terminated after 3-3.5 hours, the nitrogen is stopped, and the product is washed to obtain a mucus inert magnetically driven Janus nanomotor, recorded as Janus-MMSN-pCB, which is vacuum freeze-dried for later use.
[0025] The magnetically driven Janus nanomotor with mucus inertness of the present invention is used for mucosal delivery; this study combines mucus-penetrating particles with nanomotors, enhances the mucus-penetrating ability of nanoparticles, and provides a new carrier for mucosal delivery.
[0026] The magnetically driven Janus nanomotor (Janus-MMSN-pCB) of the present invention has a strong mucus penetration ability. In vitro experiments show that the mucus permeability of Janus-MMSN-pCB is as high as 42.59±4.17% at 4 hours under the action of a magnetic field. In addition, both the grafted pCB and the magnetic field drive enhance the mobility of Janus-MMSN-pCB in mucus, and its movement speed in mucus reaches 5.42±0.53μm / s, which is 14.11±1.38 body lengths / s. Janus-MMSN-pCB has very low toxicity to mucus-producing lung cancer cells Calu-3, has good biocompatibility, and can be effectively taken up by cells within 4 hours. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 :Schematic diagram of the synthesis and mucosal delivery of Janus-MMSN-pCB.
[0028] Figure 2 : H NMR spectrum of carboxybetaine methacrylate.
[0029] Figure 3 : Fe in Example 5 3 O 4 Transmission electron microscopy images of nanoparticles and Janus-MMSN.
[0030] Figure 4 : Fe in Example 6 3 O 4 X-ray diffraction patterns of nanoparticles and Janus-MMSN.
[0031] Figure 5 : Fe in Example 7 3 O 4 Magnetic hysteresis loops of nanoparticles and Janus-MMSN.
[0032] Figure 6 : Full scan X-ray photoelectron spectrum of Janus-MMSN in Example 8 and Fe 2p high resolution X-ray photoelectron spectrum.
[0033] Figure 7 : Nitrogen adsorption isotherm of Janus-MMSN at 77.3 K in Example 9, inset: pore size distribution diagram of Janus-MMSN.
[0034] Figure 8 : Fe in Example 10 3 O 4 Infrared spectra of nanoparticles and nanomotors.
[0035] Fig. 9 : Movement trajectory diagram of Janus-MMSN and Janus-MMSN-pCB in Example 11 with and without a magnetic field.
[0036] Fig.10 : Movement speed diagram of Janus-MMSN and Janus-MMSN-pCB in HEPES buffer and mucus in Example 11.
[0037] Fig.11 : In Example 12, Janus-MMSN and Janus-MMSN-pCB Graph of mucus penetration efficiency in the chamber.
[0038] Fig.12 : In Example 12, Janus-MMSN and Janus-MMSN-pCB Plot of apparent permeability in the cell.
[0039] Fig.13 : Evaluation of the toxicity of Janus-MMSN and Janus-MMSN-pCB to Calu-3 cells in Example 13 with or without magnetic field drive.
[0040] Fig.14: Cell imaging images of Janus-MMSN and Janus-MMSN-pCB co-cultured with Calu-3 cells for 4 h with and without magnetic field drive in Example 14. DETAILED DESCRIPTION
[0041] Example 1: Preparation of the mucus-inert magnetically driven Janus nanomotor Janus-MMSN-pCB.
[0042] 1) Amino modification of Janus-MMSN surface: A 4 mg / mL Janus-MMSN suspension was prepared in anhydrous toluene and placed in a flask, which was placed in an oil bath at 80 °C. 3-Aminopropyltriethoxysilane was added according to the mass ratio of Janus-MMSN to 3-aminopropyltriethoxysilane of 1:18, and the aminated product was obtained by reflux for 12 h and recorded as Janus-MMSN-NH 2 ;
[0043] 2) Janus-MMSN-NH 2 Surface bromination: Prepare 4 mg / mL Janus-MMSN-NH 2 The suspension was placed in an ice bath and the Janus-MMSN-NH 2 Triethylamine was added at a mass ratio of 1:8.7, and then 0.53 mg / mL α-bromoisobutyryl bromide solution was prepared with N,N-dimethylformamide and added dropwise to the reaction solution, wherein Janus-MMSN-NH 2 The mass ratio of α-bromoisobutyryl bromide to α-bromoisobutyryl bromide was 1:18.5. After reacting for 2 h with magnetic stirring, the mixture was transferred to a 30 °C water bath and reacted for 18 h. The product was washed to obtain surface brominated nanoparticles, which were denoted as Janus-MMSN-Br.
[0044] 3) Grafting pCB on the surface of Janus-MMSN-Br: N,N-dimethylformamide and water were mixed in a volume ratio of 1:1 to prepare a solution, Janus-MMSN-Br was dispersed in the above solution at a concentration of 5 mg / mL, and pCB monomer was added thereto. The mass ratio of Janus-MMSN-Br to pCB monomer was 1:23. Copper bromide and 2,2'-bipyridine were added thereto in sequence at a mass ratio of copper bromide to Janus-MMSN-Br of 1:22.5 and a mass ratio of 2,2'-bipyridine to Janus-MMSN-Br of 1:3.2. Nitrogen was passed through the solution under magnetic stirring, and then cuprous bromide was added thereto at a mass ratio of cuprous bromide to Janus-MMSN-Br of 1:7. The reaction was terminated after 3 hours, and the product was washed to obtain a mucus-inert magnetically driven Janus nanomotor, recorded as Janus-MMSN-pCB.
[0045] Example 2: Preparation of the mucus-inert magnetically driven Janus nanomotor Janus-MMSN-pCB.
[0046] 1) Amino modification of Janus-MMSN surface: A 4.5 mg / mL Janus-MMSN suspension was prepared in anhydrous toluene and placed in a flask, which was placed in an oil bath at 83 °C. 3-Aminopropyltriethoxysilane was added according to the mass ratio of Janus-MMSN to 3-aminopropyltriethoxysilane of 1:19, and the aminated product was obtained by reflux for 13 h and recorded as Janus-MMSN-NH 2 ;
[0047] 2) Janus-MMSN-NH 2 Surface bromination: Prepare 4.5 mg / mL Janus-MMSN-NH 2 The suspension was placed in an ice bath and the Janus-MMSN-NH 2 Triethylamine was added at a mass ratio of 1:8.5, and then 0.5 mg / mL α-bromoisobutyryl bromide solution was prepared with N,N-dimethylformamide and added dropwise to the reaction solution, wherein Janus-MMSN-NH 2 The mass ratio of α-bromoisobutyryl bromide to α-bromoisobutyryl bromide was 1:18. After reacting for 2.1 h with magnetic stirring, the mixture was transferred to a 35°C water bath for 17 h. The product was washed to obtain surface brominated nanoparticles, which were denoted as Janus-MMSN-Br.
[0048] 3) Grafting pCB on the surface of Janus-MMSN-Br: N,N-dimethylformamide and water were mixed in a volume ratio of 1:1.1 to prepare a solution, Janus-MMSN-Br was dispersed in the above solution at a concentration of 5.5 mg / mL, and pCB monomer was added thereto. The mass ratio of Janus-MMSN-Br to pCB monomer was 1:22. Copper bromide and 2,2'-bipyridine were added thereto in sequence at a mass ratio of copper bromide to Janus-MMSN-Br of 1:22 and a mass ratio of 2,2'-bipyridine to Janus-MMSN-Br of 1:3.1. Nitrogen was passed through the solution under magnetic stirring, and then cuprous bromide was added thereto at a mass ratio of cuprous bromide to Janus-MMSN-Br of 1:6.5. The reaction was terminated after 3.2 hours, and the product was washed to obtain a mucus-inert magnetically driven Janus nanomotor, recorded as Janus-MMSN-pCB.
[0049] Example 3: Preparation of the mucus-inert magnetically driven Janus nanomotor Janus-MMSN-pCB.
[0050] 1) Amino modification of Janus-MMSN surface: A 5 mg / mL Janus-MMSN suspension was prepared in anhydrous toluene and placed in a flask, which was placed in an oil bath at 85 °C. 3-Aminopropyltriethoxysilane was added according to the mass ratio of Janus-MMSN to 3-aminopropyltriethoxysilane of 1:18.5, and the mixture was refluxed for 14 h to obtain an amino product, which was recorded as Janus-MMSN-NH 2 ;
[0051] 2) Janus-MMSN-NH 2 Surface bromination: Prepare 5 mg / mL Janus-MMSN-NH 2 The suspension was placed in an ice bath and the Janus-MMSN-NH 2 Triethylamine was added at a mass ratio of 1:9, and then 0.55 mg / mL α-bromoisobutyryl bromide solution was prepared with N,N-dimethylformamide and added dropwise to the reaction solution, wherein Janus-MMSN-NH 2 The mass ratio of α-bromoisobutyryl bromide to α-bromoisobutyryl bromide was 1:19. After reacting for 2.3 h with magnetic stirring, the mixture was transferred to a 32°C water bath and reacted for 19 h. The product was washed to obtain surface brominated nanoparticles, which were denoted as Janus-MMSN-Br.
[0052] 3) Grafting pCB on the surface of Janus-MMSN-Br: N,N-dimethylformamide and water were mixed in a volume ratio of 1:1.05 to prepare a solution, Janus-MMSN-Br was dispersed in the above solution at a concentration of 6 mg / mL, and pCB monomer was added thereto. The mass ratio of Janus-MMSN-Br to pCB monomer was 1:24. Copper bromide and 2,2'-bipyridine were added thereto in sequence at a mass ratio of copper bromide to Janus-MMSN-Br of 1:23 and a mass ratio of 2,2'-bipyridine to Janus-MMSN-Br of 1:3.3. Nitrogen was passed through the solution under magnetic stirring, and then cuprous bromide was added thereto at a mass ratio of cuprous bromide to Janus-MMSN-Br of 1:7.5. The reaction was terminated after 3.5 hours, and the product was washed to obtain a mucus-inert magnetically driven Janus nanomotor, recorded as Janus-MMSN-pCB.
[0053] Example 4: Preparation of the mucus-inert magnetically driven Janus nanomotor Janus-MMSN-pCB.
[0054] 1) Amino modification of Janus-MMSN surface: A 4 mg / mL Janus-MMSN suspension was prepared in anhydrous toluene and placed in a flask, which was placed in an 80°C oil bath. 3-Aminopropyltriethoxysilane was added to the flask at a mass ratio of 1:18, and the mixture was refluxed for 12 h to obtain an amino product, which was recorded as Janus-MMSN-NH 2 ;
[0055] 2) Janus-MMSN-NH 2 Surface bromination: Prepare 4 mg / mL Janus-MMSN-NH 2 The suspension was placed in an ice bath and the Janus-MMSN-NH 2 Triethylamine was added at a mass ratio of 1:8.7, and then 0.53 mg / mL α-bromoisobutyryl bromide solution was prepared with N,N-dimethylformamide and added dropwise to the reaction solution, wherein Janus-MMSN-NH 2 The mass ratio of α-bromoisobutyryl bromide to α-bromoisobutyryl bromide was 1:18.7. After reacting for 2 h with magnetic stirring, the mixture was transferred to a 30°C water bath and reacted for 18 h. The product was washed to obtain surface brominated nanoparticles, which were denoted as Janus-MMSN-Br.
[0056] 3) Grafting pCB on the surface of Janus-MMSN-Br: N,N-dimethylformamide and water were mixed in a volume ratio of 1:1 to prepare a solution, Janus-MMSN-Br was dispersed in the above solution at a concentration of 5 mg / mL, and pCB monomer was added thereto. The mass ratio of Janus-MMSN-Br to pCB monomer was 1:22.5. Copper bromide and 2,2'-bipyridine were added thereto in sequence at a mass ratio of copper bromide to Janus-MMSN-Br of 1:22.5 and a mass ratio of 2,2'-bipyridine to Janus-MMSN-Br of 1:3.2. Nitrogen was passed through the solution under magnetic stirring, and then cuprous bromide was added thereto at a mass ratio of cuprous bromide to Janus-MMSN-Br of 1:7. The reaction was terminated after 3 hours, and the product was washed to obtain a mucus-inert magnetically driven Janus nanomotor, recorded as Janus-MMSN-pCB.
[0057] Example 5: Fe 3 O 4 Morphology and particle size of nanoparticles and Janus-MMSN.
[0058] The Fe prepared in Example 1 3 O 4Nanoparticles and Janus-MMSN were prepared on a double-network carbon film, and their morphology and size were observed using a JEM-2100F field emission transmission electron microscope. Figure 3 As shown, Figure 3 a is Fe 3 O 4 Transmission electron microscopy images of nanoparticles. Figure 3 b is the transmission electron microscope image of Janus-MMSN. It can be seen from the figure that Fe 3 O 4 The nanoparticles have good dispersion and the average particle size is 191nm. Janus-MMSN is composed of Fe 3 O 4 It consists of two parts: nanoparticles (black) and silica nanorods (light color), presenting a typical asymmetric Janus structure with an aspect ratio of 2:1.
[0059] Example 6: Fe 3 O 4 Crystal structure detection of nanoparticles and Janus-MMSN.
[0060] The Fe prepared in Example 1 was analyzed by powder diffraction. 3 O 4 The crystal structure of nanoparticles and Janus-MMSN was detected, and Cu target and Kα ray were selected. The X-ray diffractometer model MiniFlex600 was used to scan in the step scan mode at a speed of 0.02° / min in the range (2θ) of 10°-80°. The experimental results are shown in Figure 4 , Figure 4 a is Fe 3 O 4 X-ray diffraction spectrum of nanoparticles. Figure 4 b is the X-ray diffraction spectrum of Janus-MMSN. Fe 3 O 4 The X-ray diffraction spectrum of the nanoparticles showed Fe at diffraction angles 2θ = 30°, 35°, 43°, 53°, 57° and 63°. 3 O 4 The characteristic diffraction peaks of Fe 3 O 4 The synthesis was successful and the crystallinity was good. X-ray diffraction data of Janus-MMSN showed that the growth of mesoporous silica nanorods had little effect on Fe 3 O 4 At the same time, the spectrum shows a characteristic peak belonging to amorphous silica near 2θ=25°, proving the existence of silica.
[0061] Example 7: Fe 3O 4 Hysteresis curve determination of nanoparticles and Janus-MMSN.
[0062] The Fe prepared in Example 1 was measured at room temperature (300K) using a Lake Shore 7404 vibrating sample magnetometer in a magnetic field strength range of -20kOe-20kOe. 3 O 4 Hysteresis curves of nanoparticles and Janus-MMSN. Figure 5 As shown, Fe 3 O 4 Neither the nanoparticles nor the Janus-MMSN showed hysteresis loops, and no remanence or coercivity was detected, indicating that both had superparamagnetism. 3 O 4 The saturation magnetization of the nanoparticles is 70.13emu / g, while that of Janus-MMSN is reduced to 36.80emu / g. This indicates that there is a large amount of non-magnetic silica on the surface of Janus-MMSN. Although silica reduces the saturation magnetization of particles per unit mass, the saturation magnetization of Janus-MMSN still meets the general requirements for magnetic nanomaterials and can effectively move in response to magnetic fields.
[0063] Example 8: Surface element analysis of Janus-MMSN.
[0064] The surface of the Janus-MMSN nanomotor prepared in Example 1 was analyzed for Fe, O, Si and C using an X-ray photoelectron spectroscopy (XPS) analyzer of model ESCALAB 250XI. The experimental results are shown in Figure 6 As shown, Figure 6 a is the full scan XPS spectrum of Janus-MMSN, Figure 6 b is the Fe 2p high-resolution XPS spectrum of Janus-MMSN. Figure 6 The absorption peaks at 102.5 eV and 154.0 eV in a are respectively attributed to SiO 2 The spectral data show that Fe element exists on the surface of Janus-MMSN, indicating that Fe 3 O 4 Not SiO 2 Completely wrapped. Combined Figure 6 b, Fe 2p splits into two peaks at 710.6eV and 724.6eV, which are respectively attributed to Fe 3 O 4 These results indicate that SiO2 and Fe 3 O 4 Composition of Janus-MMSN nanoparticles.
[0065] Example 9: Determination of nitrogen isothermal adsorption-desorption curve of Janus-MMSN.
[0066] The Janus-MMSN prepared in Example 1 was vacuum degassed and its nitrogen isothermal adsorption-desorption curve was measured at 77K using a TriStarII3020 specific surface area and porosity analyzer. The specific surface area of Janus-MMSN was calculated using the Brunauer-Emmett-Teller equation, and the pore size was obtained based on the adsorption branch of the Barrett-Joyner-Halenda pore size distribution curve and the P / P 0 The pore volume was measured at a relative pressure of >0.99. Figure 7 As shown in the figure, the inset is the pore size distribution diagram of Janus-MMSN. The nitrogen adsorption isotherm of Janus-MMSN belongs to the type IV adsorption isotherm in the IUPAC classification, which is a typical adsorption curve of mesoporous materials. According to the inset, the mesopore diameter of Janus-MMSN is about 3.12nm. In addition, the specific surface area and total pore volume of Janus-MMSN are as high as 338.3m 2 / g and 0.5295cm 3 / g, indicating that Janus-MMSN has a larger cargo load space.
[0067] Example 10: Fe 3 O 4 Nanoparticles, Janus-MMSN, Janus-MMSN-NH 2 Chemical structure determination of Janus-MMSN-Br and Janus-MMSN-pCB.
[0068] Fourier transform infrared spectroscopy was used at a wavelength of 400-4000cm -1 The Fe prepared in Example 1 3 O 4 Nanoparticles, Janus-MMSN, Janus-MMSN-NH 2 The chemical structures of Janus-MMSN-Br and Janus-MMSN-pCB were characterized. Figure 8 As shown, Figure 8 a is Fe 3 O 4 Infrared spectrum of nanoparticles. Figure 8 b is the infrared spectrum of Janus-MMSN, Figure 8c is Janus-MMSN-NH 2 Infrared spectrum of Figure 8 d is the infrared spectrum of Janus-MMSN-Br, Figure 8 e is the infrared spectrum of Janus-MMSN-pCB. 3 O 4 In the infrared spectrum of nanoparticles, 575 cm -1 There is an obvious Fe-O vibration characteristic absorption peak. In the infrared spectrum of Janus-MMSN, 459cm -1 and 1080cm -1 The absorption peaks at 2 Si-O bending vibration absorption peak and Si-O-Si antisymmetric stretching vibration absorption peak. Janus-MMSN-NH 2 The infrared spectrum of 1630cm -1 The in-plane bending vibration absorption peak of NH appears at 2850cm -1 and 2920cm -1 -CH 2 -antisymmetric and symmetric stretching vibration absorption peaks, indicating the successful amination of Janus-MMSN. The carbonyl peak of α-bromoisobutyryl bromide did not appear in the spectrum of Janus-MMSN-Br, but it was consistent with the infrared spectrum results obtained by Lee et al. after modifying α-bromoisobutyryl bromide on filter paper (Materials, 2015, 8(9): 5647-5670). After initiating pCB polymerization on the surface of Janus-MMSN-Br, the carbonyl peak of α-bromoisobutyryl bromide was 1735 cm -1 The characteristic absorption peak of C=O stretching vibration appeared at , proving that the nanomotor was successfully grafted onto pCB.
[0069] Example 11: In vitro mucus motility assay of Janus-MMSN and Janus-MMSN-pCB.
[0070] Preparation buffer: 238.3 mg 4-hydroxyethylpiperazineethanesulfonic acid (HEPES) and 292.2 mg NaCl were dissolved in 50 mL deionized water to prepare 20 mM HEPES buffer, and the pH was adjusted to 7.4 with 1 M NaOH solution and passed through a membrane, and stored at 4°C. Type II (partially purified) porcine gastrointestinal mucin (60 mg / mL), lecithin (3.2 mg / mL) and BSA (32 mg / mL) were dissolved in 20 mM HEPES (pH 7.4) buffer, and incubated at 4°C and 100 rpm for 48 hours to obtain simulated mucus. Janus-MMSN and Janus-MMSN-pCB synthesized in Example 1 were fluorescently labeled with fluorescein isothiocyanate (FITC). FITC and aminopropyltriethoxysilane were dissolved in anhydrous ethanol at a mass ratio of 1:1 at room temperature, and the reaction was stirred in the dark for 12 hours. The resulting products were mixed with Janus-MMSN and Janus-MMSN-pCB, respectively, and reacted with magnetic stirring for 24 hours in the dark. The diffusion movement of fluorescently labeled Janus-MMSN and Janus-MMSN-pCB in mucus was observed by multi-particle tracking experiments, and a gradient magnetic field was created around them by vector electromagnets. A 1 mg / mL nanomotor solution was mixed with an equal volume of mucus, allowed to stand for 3 minutes, and then dropped onto a glass slide. The movement of the nanomotor in HEPES buffer and mucus was observed by an inverted fluorescence microscope, and the effect of magnetic field drive on the diffusion behavior of the nanomotor was studied by turning on / off the vector electromagnet. The motion trajectory of the nanomotor was recorded by a camera equipped with a microscope. At least three independent experiments were performed for each condition, and the trajectories of n≥10 nanomotors were analyzed in each experiment. The motion characteristics of the nanomotor were analyzed using ImageJ software. The motion trajectory of the nanomotor is shown in the attached Fig. 9 , Fig. 9 a is the motion trajectory of the nanomotor in the absence of a magnetic field. Fig. 9 b is the motion trajectory of the nanomotor in the magnetic field. In addition, the data of the motion speed of the nanomotor is shown in the attached Fig.10 From the attached Fig. 9 a It can be seen that in the absence of magnetic field driving, Janus-MMSN and Janus-MMSN-pCB mainly perform Brownian motion in HEPES buffer and mucus, and their motion trajectory is almost a point. When a gradient magnetic field with an intensity of 20mT is applied around them, that is, Fig. 9 b, Janus-MMSN and Janus-MMSN-pCB were driven by the magnetic field and moved in the HEPES buffer and mucus along the magnetic field, showing a long movement trajectory. Fig. 9The results show that the nanomotors Janus-MMSN and Janus-MMSN-pCB can overcome Brownian motion and perform magnetically driven motion under magnetic field. Fig.10 Compared with HEPES buffer, mucus has a significant blocking effect on the movement of nanomotors. Both pCB grafting and magnetic drive can effectively accelerate the movement of nanoparticles in mucus. Under magnetic field drive, the movement speed of Janus-MMSN-pCB in mucus is 5.42±0.53μm / s, which is 14.11±1.38 body lengths / s. These results show that Janus-MMSN-pCB has strong mucus movement ability.
[0071] Example 12: In vitro mucus penetration ability assay of Janus-MMSN and Janus-MMSN-pCB.
[0072] Using a polycarbonate membrane with a pore size of 3.0 μm The mucus penetration performance of FITC-labeled Janus-MMSN and Janus-MMSN-pCB prepared in Example 11 in the presence or absence of a magnetic field was measured in a small chamber. First, 20 μL of mucus was added to the upper chamber, and 600 μL of HEPES buffer was added to the lower chamber. Then 200 μL of solutions of different fluorescently labeled nanomotors (1 mg / mL, prepared with HEPES buffer) were added to the upper chamber, and the device was cultured in a 37°C incubator. Samples (100 μL) were taken from the receptor chamber at fixed time points (0.5, 1, 1.5, 2, 3 and 4 h), and an equal amount of HEPES buffer was added. The fluorescence intensity of the nanomotor-containing solution taken out was analyzed by a multifunctional microplate reader under 485 nm excitation light, and the apparent permeability coefficient (P) of the nanomotor in mucus was calculated using the following formula app ):
[0073]
[0074] Where dQ / dt represents the mucus penetration rate of the nanomotor, C 0 is the initial concentration of nanomotors, A is the membrane area (cm 2 ). Janus-MMSN and Janus-MMSN-pCB The mucus permeability and apparent permeability coefficient in the chamber are Fig.11 and 12As shown. The mucus permeability curve shows that in the absence of a magnetic field, due to the modification of pCB, the mucus permeability of Janus-MMSN-pCB at 4h reached 35.05±1.90%, which was significantly higher than that of Janus-MMSN without pCB modification (6.51±0.38%). In addition, under the drive of an external magnetic field (20mT), the mucus permeability of Janus-MMSN-pCB increased to 42.59±4.17%, indicating that the application of a magnetic field can further enhance the mucus penetration ability of the magnetically driven nanomotor and promote its diffusion in the mucus. Fig.12 It can be seen that under magnetic field driving, the apparent permeability coefficient of Janus-MMSN-pCB in mucus is 53.70×10 -6 cm / s, which is higher than the mucus-penetrating nanoparticles with surface modified zwitterionic polymers reported in the literature (12×10 -6 -30×10 -6 cm / s) (Acs Applied Materials&Interfaces, 2016, 8(38): 25444-25453; Journal of Colloid and Interface Science, 2020, 582, 364-375; Fe 3 O 4 Preparation, characterization and performance study of / PDA / chitosan magnetic microspheres. Lanzhou Jiaotong University), which shows that Janus-MMSN-pCB has a strong ability to quickly penetrate the mucus layer.
[0075] Example 13: Cytotoxicity evaluation of Janus-MMSN and Janus-MMSN-pCB.
[0076] Calu-3 cells that produce mucus were selected as model cells. The culture medium was mainly MEM medium, which also included 10% fetal bovine serum, 100 U / mL penicillin and 100 μg / mL streptomycin. The cells were kept at 37°C and 5% CO 2 The cells were cultured in an environment of 50% and subcultured when the cell confluence reached more than 80%. The cytotoxicity of Janus-MMSN and Janus-MMSN-pCB prepared in Example 1 was determined by MTT colorimetry. Calu-3 cells in the logarithmic growth phase were seeded into a 96-well plate at a density of 8000 cells / well, with a volume of 80 μL per well, and placed at 37°C and 5% CO 2Incubator for 24 hours. Then, 20 μL of nanomotor solution of different concentrations (10, 25, 50 and 100 μg / mL, prepared with Dulbecco's phosphate buffer (DPBS)) or DPBS buffer (control group) was incubated with the cells for 4 hours, and then 20 μL of MTT solution (5.5 mg / mL, prepared with DPBS buffer, pH = 7.4) was added to each well under light-proof conditions, and the cells were further incubated for 4 hours. After centrifuging the 96-well plate at 1500 rpm for 10 minutes, the supernatant was discarded, and 100 μL of dimethyl sulfoxide was added to each well. The plate was placed on a shaker at 37°C for 20 minutes under light-proof conditions. The absorbance at a wavelength of 570 nm was measured using the Infinite M200 PRO multifunctional microplate reader, and the cell survival rate was calculated by comparing the absorbance of treated and untreated cells. The experimental results are shown in Fig.13 Without external magnetic field drive, Janus-MMSN and Janus-MMSN-pCB had almost no effect on cell activity, and when the nanoparticle concentration reached 100μg / mL, the cell survival rate was still above 80%. After applying a magnetic field, the toxicity of Janus-MMSN and Janus-MMSN-pCB to Calu-3 cells increased, but even at a concentration of up to 100μg / mL, the cell survival rate was still above 70%, indicating that the nanomotors have low toxic side effects on cells and have good biocompatibility.
[0077] Example 14: Detection of the cellular uptake effect of Janus-MMSN and Janus-MMSN-pCB.
[0078] Calu-3 cells in logarithmic growth phase were seeded into 6-well plates at a density of 5000 cells / well, with a volume of 2 mL per well, and incubated at 37°C and 5% CO 2 Incubator for 48 hours. Then, take 700 μL of FITC fluorescently labeled nanomotor solution (50 μg / mL, prepared with DPBS buffer) prepared in Example 11 and add it to the well and continue to culture for 4 hours. Then, aspirate the liquid in the well plate, rinse it 3 times with DPBS buffer, and then stain it with 700 μL of H33258 staining solution (5 μg / mL, prepared with DPBS buffer) for 30 minutes. Finally, aspirate the staining solution and gently rinse it 3 times with DPBS buffer. Use a fluorescent inverted microscope to observe the uptake of nanomotors by Calu-3 cells. The experimental results are shown in Fig.14After superimposing the bright field image and the fluorescence image, green fluorescence can be clearly observed in the cytoplasm, indicating that Calu-3 cells have successfully taken up the nanomotors. Comparing the fluorescence images, it can be seen that regardless of whether a magnetic field is applied, the uptake of Janus-MMSN-pCB by Calu-3 cells is significantly higher than that of Janus-MMSN. After the introduction of an external magnetic field, the cellular uptake of Janus-MMSN and Janus-MMSN-pCB is higher than that under the condition of no magnetic field, indicating that both zwitterionic polymer pCB and magnetic field drive can promote the uptake of nanomotors by Calu-3 cells. This shows that both nanomotors can enter cells efficiently, and Janus-MMSN-pCB has a better cellular uptake effect.
[0079] In summary, the present invention aims at the mucus barrier problem existing in the mucosal delivery process and proposes a method based on Fe 3 O 4 The Janus magnetically driven nanomotor composed of nanoparticles and mesoporous silica nanorods was used to construct a magnetically driven Janus nanomotor Janus-MMSN-pCB with mucus inertness. The mucus inertness of the nanomotor comes from the zwitterionic polymer pCB with equal anionic and cationic groups and superhydrophilicity grafted on the surface of the mesoporous silica nanorods. The electrical neutrality and superhydrophilicity of pCB can effectively weaken the adhesion of the nanomotor to the mucus layer, thereby accelerating the delivery of the nanomotor in mucus, and the autonomous movement of the nanomotor generated by magnetic drive further enhances its ability to penetrate mucus. The movement speed of Janus-MMSN-pCB in mucus is as high as 5.42±0.53μm / s, which is 14.11±1.38 body lengths / s. In addition, the mucus penetration efficiency of Janus-MMSN-pCB driven by magnetic field is as high as 42.59±4.17% at 4h. In vitro cell experiments show that Janus-MMSN-pCB has good biocompatibility and can be effectively taken up by cells. The mucus inert magnetically driven nanomotor Janus-MMSN-pCB provides a new carrier for mucosal delivery. It has been described through the preferred embodiments of the present invention, and the relevant technical personnel can obviously modify or appropriately change and combine the methods described herein without departing from the content, spirit and scope of the present invention to implement the technology of the present invention. It should be particularly pointed out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the spirit, scope and content of the present invention.
Claims
1. A magnetically driven Janus nanomotor with mucus inertness; characterized in that: The zwitterionic polymer polycarboxybetaine methacrylate pCB was grafted onto the mesoporous silica surface of the Janus nanomotor driven by a magnetic field MF, which was composed of Fe3O4 nanoparticles and mesoporous silica nanorods MSN; the mucus-inert magnetically driven Janus nanomotor was denoted as Janus-MMSN-pCB.
2. The method for preparing the magnetically driven Janus nanomotor with mucus inertness of claim 1, characterized in that: The steps include: 1) Amino modification of Janus-MMSN surface: 4-5 mg / mL Janus-MMSN suspension was prepared in anhydrous toluene and placed in a flask, which was placed in an oil bath at 80-85°C. 3-aminopropyltriethoxysilane was added thereto at a mass ratio of Janus-MMSN to 3-aminopropyltriethoxysilane of 1:18-19, and the mixture was refluxed for 12-14 h to obtain an amino product, which was recorded as Janus-MMSN-NH2; 2) Surface bromination of Janus-MMSN-NH2: 4-5 mg / mL Janus-MMSN-NH2 suspension was prepared with N,N-dimethylformamide and placed in an ice bath, triethylamine was added according to the mass ratio of Janus-MMSN-NH2 to triethylamine of 1:8.5-9, and then 0.5-0.55 mg / mL α-bromoisobutyryl bromide solution was prepared with N,N-dimethylformamide and added dropwise to the reaction solution, wherein the mass ratio of Janus-MMSN-NH2 to α-bromoisobutyryl bromide was 1:18-19, and the reaction was stirred magnetically for 2-2.3 hours and then transferred to a 30-35°C water bath for 17-19 hours, and the product was washed to obtain surface brominated nanoparticles, which were recorded as Janus-MMSN-Br; 3) Grafting pCB on the surface of Janus-MMSN-Br: N,N-dimethylformamide and water were mixed in a volume ratio of 1:1-1.1 to prepare a solution, Janus-MMSN-Br was dispersed in the above solution at a concentration of 5-6 mg / mL, and pCB monomer was added thereto, the mass ratio of Janus-MMSN-Br to pCB monomer was 1:22-24, and the mass ratio of copper bromide to Janus-MMSN-Br was 1:22- 23 and the mass ratio of 2,2'-bipyridine to Janus-MMSN-Br is 1:3.1-3.
3. Copper bromide and 2,2'-bipyridine are added thereto in sequence, and nitrogen is passed through under magnetic stirring. Then, cuprous bromide is added thereto at a mass ratio of cuprous bromide to Janus-MMSN-Br of 1:6.5-7.
5. The reaction is terminated after 3-3.5 hours, and the product is washed to obtain a mucus-inert magnetically driven Janus nanomotor, which is recorded as Janus-MMSN-pCB.
3. The method according to claim 2, wherein the mass ratio of Janus-MMSN-NH2 to α-bromoisobutyryl bromide is 1:18.5-19.
4. The method according to claim 2, characterized in that The mass ratio of Janus-MMSN-Br to pCB monomers was 1:22-23.
5. The magnetically driven Janus nanomotor with mucus inertness prepared in claim 1, characterized in that The mucus-inert magnetically driven Janus nanomotor has the ability to resist adsorption by the mucus layer and can quickly move through the mucus layer in a magnetic field. Its mucus permeability is as high as 42.59% in 4 hours under magnetic field drive, and its movement speed in mucus reaches 5.42±0.53μm / s, which is 14.11±1.38 body lengths / s.
6. The magnetically driven Janus nanomotor with mucus inertness prepared according to claim 1, characterized in that The mucus-inert magnetically driven Janus nanomotors have low toxicity to mucus-producing Calu-3 cells and can be efficiently taken up by Calu-3 cells within 4 h.
7. Use of the magnetically driven Janus nanomotor with mucus inertness according to claim 1 in the preparation of mucosal delivery drugs.
Citation Information
Patent Citations
Active nanoparticles and method of using
US20090226521A1